Iron Overload in Transfusion-Dependent Indonesian Thalassemic Patients. (15th April 2021) - Fianza, Pandji Irani; Rahmawati, Anita; Widihastha, Sri Hudaya; Afifah, Shofura; Ghozali, Mohammad; Indrajaya, Andre; Pratama, Dilli Marayuzan Akbar; Prasetya, Dimmy; Sihite, Teddy Arnold; Syamsunarno, Mas Rizky A. A.; Setiabudi, Djatnika; Fucharoen, Suthat; et al.
Abstract : Thalassemia is a genetic disease caused by disruption of globin chain synthesis leading to severe anemia and thus regular blood transfusion is necessary. However, there have been known transfusions-related consequences, including iron overload and multi-organ damage. The aims of this study were to evaluate liver and cardiac function in youth and adult transfusion-dependent Indonesian thalassemic patients and to assess its correlation with serum ferritin levels, as well as T2 ∗ magnetic resonance imaging (MRI). Transfusion-dependent thalassemic (TDT) outpatients ( n = 66; mean age, 21.5 ± 7.2 years) were carried out for the complete assessment consisting of blood test including liver enzyme and serum ferritin, followed by electrocardiography (ECG) and echocardiography. Subjects were also divided by serum ferritin levels into three groups: < 2500 ng/mL, 2500–5000 ng/mL, and >5000 ng/mL. Additionally, subgroup analysis in patients with T2 ∗ MRI assessment was conducted. In terms of age of first blood transfusion, subjects with ferritin >5000 ng/mL were the youngest among others. The alanine aminotransferase (ALT) levels in group with serum ferritin >5000 ng/mL were significantly higher than those of the group with serum ferritin <2500 ng/mL. Additionally, youth and adult TDT patients whose serum ferritin >5000 ng/mL had significantly lower tricuspid annular plane systolic excursion (TAPSE) when compared with those who had serum ferritin <2500 ng/mL. Similarly, TAPSE in patients with moderate cardiac siderosis based on cardiac T2 ∗ MRI was significantly lower than those without cardiac siderosis. There was significant, but only moderate correlation between serum ferritin and cardiac T2 ∗ MRI. Based on these findings, it is important to routinely monitor iron accumulation-related complications, including liver and cardiac damage in youth and adult TDT patients.